A note on primary spectrum over commutative rings - (:unkn) unknown (Sciendo, 2018)
In this work we define a primary spectrum of a commutative ring R with its Zariski topology T. We introduce several properties and examine some topological features of this concept. We also investigate differences between the prime spectrum and our primary spectrum. © 2018, Sciendo. All rights reserved.
Keywords: Primary ideal; Primary spectrum; Zariski topology